Drug repositioning: current approaches and their implications in the precision medicine era. Issue 1 (2nd January 2018) - Talevi, Alan
ABSTRACT: Introduction : Drug repositioning implies finding new medical uses for existing drugs. It represents a cost-efficient approach, since the new indications are built on the basis of available information on pharmacokinetics, safety and manufacturing. Whereas most of the pioneering drug repurposing stories arose from serendipitous observations and clever exploitation of side effects, the drug discovery community has lately addressed repurposing initiatives in a more systematic manner. Today, in the middle of the omics era, we have the tools to explore drug repurposing opportunities in a tailored, personalized manner. Areas covered : After a brief discussion on modern approaches to drug repurposing, the author connects the philosophies of drug repurposing and personalized medicine through the well-known and extended practice of off-label prescription. The author also discusses which, among current systematic repurposing approaches, are more appropriate to be integrated with the field of precision medicine. Expert commentary : Personalized drug repurposing is not a new concept at all: for years, it has been known as off-label prescription, a practice widely accepted especially in some branches of medicine. Whereas in the past such approach was in many cases supported by empiric knowledge, today omics technologies allow us to face novel personalized drug repurposing options in a systematic manner.